Species boundaries in the human pathogen Paracoccidioides (2017)
The use of molecular taxonomy for identifying recently diverged species has transformed the study of speciation in fungi. The pathogenic fungus Paracoccidioides spp has been hypothesized to be composed of five phylogenetic species, four of which compose the brasiliensis species complex. Nuclear gene genealogies support this divergence scenario, but mitochondrial loci do not; while all species from the brasiliensis complex are differentiated at nuclear coding loci, they are not at mitochondrial loci. We addressed the source of this incongruity using 11 previously published gene fragments, 10 newly-sequenced nuclear non-coding loci, and 10 microsatellites. We hypothesized and further demonstrated that the mito-nuclear incongruence in the brasiliensis species complex results from interspecific hybridization and mitochondrial introgression, a common phenomenon in eukaryotes. Additional population genetic analyses revealed possible nuclear introgression but much less than that seen in the mitochondrion. Our results are consistent with a divergence scenario of secondary contact and subsequent mitochondrial introgression despite the continued persistence of species boundaries. We also suggest that yeast morphology slightly—but significantly—differs across all five Paracoccidioides species and propose to elevate four of these phylogenetic species to formally described taxonomic species.